Transforming human resource functions with automation - Pathak, Anchal; Pathak, Anchal, 1985-; Rana, Shikha, 1984- (Hershey, PA: Business Science Reference, 2021)
"This book is a collection of research on the methods and applications of artificial intelligence and autonomous systems within human resource management and modern alterations that are occurring"--
Includes bibliographical references and index.
Keywords: Personnel management -- Technological innovations; Manpower planning